Managing Director's Global Policy Agenda to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2014)
The latest snapshot of the global economy looks uneasily familiar: a brittle, uneven recovery, with slower-than-expected growth and increasing downside risks. Bold and resolutely executed policies are needed to prevent growth from settling into a 'new mediocre,' with unacceptably low job creation and inclusion. Measures should emphasize: lifting growth, building resilience, and achieving coherence. The IMF will help members deliver on this policy agenda by redeploying resources toward lending and capacity building for members facing pressing challenges; strengthening macro-financial surveillance; providing policy advice and analysis on managing the impending monetary normalization, including on deploying macro-prudential tools; and implementing growth-friendly fiscal policies and macro-critical structural reforms. Staff will also build on existing work and develop options for next steps should ratification of the 2010 reforms be delayed beyond year end.